Job search and career checklists : 101 proven time-saving checklists to organize and plan your career search - Hirsch, Arlene S., 1951- (JIST Works, 2005)
The thought of looking for a job is daunting to some people where do they start? So imagine how helpful it would be to have a series of checklists to help them get started and organize their time and tasks. Job seekers gain immediate confidence by following these "to do" checklists. They know they've covered all their bases which leaves them more time to concentrate on important skills and tasks such as networking and interviewing. Whether starting a new career or analyzing present job progress, readers will find this book a great tool for assessing needs, gaining confidence in all job-hunting